Temple portals : studies in aggadah and midrash in the Zohar - Yiśreʼeli, ʻOded (Studia Judaica (Walter de Gruyter & Co.), 2016)
This monograph discusses the Zohar, the most important book of the Kabbalah, as a late strata of the Midrashic literature. The author concentrates on the 'expanded' biblical stories in the Zohar and on its relationship to the ancient Talmudic Aggadah. The analytical and critical examination of these biblical themes reveals aspects of continuity and change in the history of the old Aggadic story and its way into the Zoharic corpus.